A Study on Language Learning Strategy with Its Classification and Training Model: Exploring the Effectiveness of Language Learning Strategies in EFL Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This review paper discusses the literature on language learning strategies, Elaborate classification systems for learner strategies have also been created to explain the knowledge extracted from concise research that aim to map the complex permutations and sometimes imprecise meanings of the learner's self-reported techniques teaching model, and to illustrate the value of language learning strategy to English as a Foreign Language (EFL) which is effective language learning strategy training model that is beneficial each to EFL Learners instructor is badly required. Previous researchers using their own findings to define language learning strategies, to focus on criteria derived from first-language studies, or to build a detailed comprehensive of learning strategies derived from several sources.